2018
DOI: 10.3390/su10072346
|View full text |Cite
|
Sign up to set email alerts
|

Startups’ Roads to Failure

Abstract: The role of a relatively small cadre of high-tech startup firms in driving innovation and economic growth has been well known and amply celebrated in recent history. At the same time, it is well recognized that, while the overall contribution of startups is crucial, the high-risk and high-reward strategy followed by these startups leads to significant failure rates and a low ratio of successful startups. So, it is curious to notice that literature tends to focus on successful startups and on quantitative studi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
60
0
8

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 139 publications
(111 citation statements)
references
References 45 publications
(69 reference statements)
2
60
0
8
Order By: Relevance
“…These difficulties may have arisen because the products are still not able to compete with existing players, or due to the company's inability to read market desires. This point is becoming significance and inline with the finding of Kulicke and Kripp (2013) and also Cantamessa et al (2018) that points out one of the causes of startup failure is failing to compete. 3.…”
Section: Problems Encounteredsupporting
confidence: 73%
See 1 more Smart Citation
“…These difficulties may have arisen because the products are still not able to compete with existing players, or due to the company's inability to read market desires. This point is becoming significance and inline with the finding of Kulicke and Kripp (2013) and also Cantamessa et al (2018) that points out one of the causes of startup failure is failing to compete. 3.…”
Section: Problems Encounteredsupporting
confidence: 73%
“…The last obstacle according to this study is the external environment constraints of the business, in the form of trends that must be followed or created, the demands of the markets that have been fulfilled, legal compliance demands that must be followed and other external demands which are challenges that are not easy to overcome (Salamzadeh & Kawamorita, 2015). Some of the obstacles faced by startups based on this study are where startups experience constraints in the HR field, competition challenges, marketing difficulties, in line with the findings of the obstacles faced by startups that are the cause of their bankruptcy which has been investigated by (Bednar et al, 2018;Cantamessa et al, 2018;Triebel, 2018b) and CB Insight (2019) and have been described in Table 3.…”
Section: Lack Of Quality Of Incubation Programssupporting
confidence: 71%
“…The former indicates a level at which an entrepreneur wants to maintain a minimum livelihood while doing what he or she wishes to do. By contrast, the latter means the level at which an entrepreneur wants to achieve a high level of financial achievement and social reputation [12]. Moreover, based on startup indicators by country, the motivations for startups are classified as economic and non-economic motivations.…”
Section: The Startup Business In the New Economy And Marketsmentioning
confidence: 99%
“…Creating a new business is a process fraught with difficulties and failure [9][10][11][12]. Moreover, the cognitive orientation of potential entrepreneurs has a significant influence on their willingness to persist in their entrepreneurial activity in the face of these difficulties.…”
Section: Introductionmentioning
confidence: 99%
“…Venture funds, on the other hand, take responsibility for their investors, therefore they take a more rational approach to making decisions: they evaluate how the market reacts to new products and conduct a full audit of a specific project. In (Cantamessa et al, 2018), the authors analyzed 214 reports on completed projects and concluded that the key factor in the failure of the project is the lack of a business development strategy. It was shown in (Damodaran, 2009) that even those young development companies that are profitable depend on private capital, the initial savings of owners, venture capital and the  the need for significant material and labor costs for the development and implementation of projects;  uncertainty of the target audience of projects;  limited financial, operational information at the stage of development of the technical specifications of projects;  the high final cost of projects and their scale, which narrows the potential circle of buyers, since such projects are often not relevant in small and medium-sized businesses;  the need to adapt projects to broaden market niches.…”
Section: Problem Of Assessing the Investment Attractiveness Of Risk Pmentioning
confidence: 99%